Organisational Forms in Professional Cycling: Efficiency Issues of the UCI Pro Tour - Luca Rebeggiani; Davide Tondani (Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2006)
This paper gives a first economic approach to pro cycling and analyses the changes induced by the newly introduced UCI Pro Tour on the racing teams? behaviour. We develop an oligopolistic model starting from the well known Bertrand and Cournot frameworks to analyse if the actual setting of the UCI Pro Tour leads to a partially unmeant behaviour of the racing teams. In particular, we show that the blamed regional concentration of their race participation depends on a lack of incentives stemming from the licence assignation procedure. Our theoretical results are supported by empirical data concerning the performance of the racing teams in 2005. As a recommendation for future improvements, we derive from the model the need for a relegation system for racing teams. – – Der Aufsatz stellt die erste ökonomische Analyse des professionellen Radsports dar. Er analysiert insbesondere die Anreizwirkungen der neuen UCI Pro Tour auf Teams und Fahrer. Ausgehend von den bekannten Bertrand- und Cournot-Ansätzen entwickeln wir ein einfaches Oligopol-Modell, um zu untersuchen, ob die derzeitige Pro Tour-Organisation zu einem unerwünschten Verhalten der Teilnehmer führt. Wir zeigen, dass insbesondere das Problem der geographischen Konzentration der Rennteilnahmen der Teams von den mangelnden Anreizen abhängt, die vom jetzigen Lizenzvergabesystem ausgehen. Unsere theoretischen Ergebnisse werden durch empirische Daten aus der Pro Tour 2005 gestützt. Als Empfehlung für zukünftige Entwicklungen leiten wir aus dem Modell die Notwendigkeit einer Öffnung der Pro Tour ab, mit Auf- und Abstiegsmöglichkeiten für Rennteams.
Keywords: D43; L83; 330; Sports economics; professional cycling; oligopolistic competition